Unique School and Rural Education in the New State in Portugal - Magalhães, Justino (Historia y Memoria de la Educación, 2018)
The Unique Portuguese School did not establish a qualitatively uniform relationship with culture and society. The issue of education often presented a contrast between the rural world, taken as idyllic, and the urban world, presented as threatening to the morale and well-being of individuals. Correlatively, the school curriculum showed an openness to progress and cosmopolitanism. Rural culture, the material universe, and the symbolic countryside of rural Portugal were neglected and seen as being archaic. This indeterminacy and that paradox were based on ideological and nationalistic assumptions, and had their consequences in school norms and in the corporatism of the Estado Novo. The portugality underlying the Unique School would not necessarily be rural, but the minimalist formation provided by school literacy seemed compatible with rurality. I propose to document and problematize this subject. I will also refer to policies for expanding the school network and teacher training. I will conclude by examining the International Survey promoted by the UNESCO, Possibilités d’Accès à l’Éducation dans les Zones Rurales (1958), in response to which the Portuguese State has issued the laconic answer «aucune différence». This would seem to show the possibilities of the Portuguese unique school